X-ray microfluorescence as a tool to analyze elemental changes in femur head induced by chemotherapy drugs for the treatment of breast cancer. (November 2015) - Pickler, A.; Mota, C.L.; Mantuano, A.; Salata, C.; Nogueira, L.P.; Almeida, A.P.; Alessio, R.; Sena, G.; Braz, D.; de Almeida, C.E.V.; Barroso, R.C.
Abstract: Recently some developments in a large number of investigative techniques have been made with the objective to obtain a micrometer spatial resolution imaging of elemental concentrations. The X-ray microfluorescence analysis (µXRF) is one of those techniques which is based on the localized excitation of a small area on the surface of sample, providing information of all elements contained in the material under study. Breast cancer is the most common malignancy in Brazilian women. The main treatment strategies for the breast cancer are surgery and chemotherapy. As bone loss is one of the possible chemotherapy side effects, in this work was used μXRF technique on femoral head samples of female Wistar rats to evaluate Ca, Fe and Zn concentrations in order to investigate possible elemental changes in bone caused by the chemotherapy. Fifteen female rats were divided randomly in groups (five rats each). G1 group received doses of doxorubicin/cyclophosphamide drugs and G2 group was treated with docetaxel/cyclophosphamide drugs. µXRF measurements were carried out at the X-ray XRF beamline in the Brazilian Synchrotron Light Laboratory. The results showed significant decrease especially in Ca concentrations when comparing the treated groups with the control group. Highlights: One of the side effects caused by chemotherapy drugs is a significant bone loss. Metals in human provide insights into individual exposure and/or disease. We applied μXRF in samples of Wistar rats to evaluate the elemental concentrations.